Acquired CNS Demyelinating Syndrome in Children Referred to Shiraz Pediatric Neurology Ward - INALOO*, Soroor; HAGHBIN, Saeedeh; MORADI, Mehrpoor; DASHTI, Hassan; Nazila SAFARI, Nazila (Iranian Journal of Child Neurology, 2014)
How to Cite This Article: Inaloo S, Haghbin S, Moradi M, Dashti H, Safari N. Acquired CNS Demyelinating Syndrome in Children Referred to Shiraz Pediatric Neurology Ward. Iran J Child Neurol. 2014 Spring; 8(2):18-23. Objective Incidence of CNS acquired demyelinating syndrome (ADS), especially multiple sclerosis (MS) in children, appears to be on the rise worldwide. The objective of this study was to determine prevalence, clinical presentation, neuroimaging features, and prognosis of different types of ADS in Iranian children. Materials & Methods During the period 2002-2012, all the patients (aged 1-18 years) with ADS, such as MS, acute disseminated encephalomyelitis (ADEM), optic neurotic (ON), Devic disease, and transverse myelitis (TM), referred to the pediatric neurology ward, Nemazee Hospital, Shiraz University of Medical Sciences, were included in this study. Demographic data, clinical signs and symptoms, past and family history, preclinical findings, clinical course, and outcome were obtained. Results We identified 88 patients with ADS in our center. The most prevalent disease was MS with 36.5% (n=32), followed by AEDM 26.1% (n=31), ON 17% (n=13), TM 15.9% (n=14), and Devic disease 4.5% (n=4). MS, ON, TM were more common among females while ADEM was more common in males. Children with ADEM were significantly younger than those with other types of ADS. Family history was positive in 10% of patients with MS. Previous history of recent infection was considerably seen in cases with ADEM. Clinical presentation and prognosis in this study was in accordance with those in previous studies on children. Conclusion In this study, the most common type of ADS was MS, which was more common in female and older age cases. ADEM was more common in male and younger children. ADEM and ON had the best and Devic disease had the worst prognosis. References 1. Longer-Gould A, Zhaug JL, Chung J, Yeung Y, Wanbant E, Yao J. Incidence of acquired CNS demyelinating syndrome in a multiethnic cohort of children. Neurology 2011;27(12):1143-8. 2. Banwell B, Kennedy J, Sandovnick D, Arnold DL, Magalhaes S, Wambera K. Incidence of acquired demyelination of the CNS in Canadian children. Neurology 2009;72(3):232-9. 3. Canellas AR, Gols AR, Izquierdo J.R, Subirana MT, Gairin XM. Idiopathic inflammatory demyelinating disease of central nervous system. Neuroradiology 2007;49(5):393-409. 4. Renoux C, Vukusic S, Mikaeloff Y. Natural history of multiple sclerosis with childhood onset. N Engl Med 2007;356(25):2603-13. 5. Krupp LB, Banwell B, Tenembaum S; International Pediatric MS Study Group. Consensus definition proposed for pediatric multiple sclerosis and related disorders. Neurology 2007;68(16 Suppl 2):S7-12. 6. Ebers GC. Environmental factors and multiple sclerosis. Lancet Neurol 2008;77(3):268-77. 7. Banwell B, Ghezzi A, Bar-OrA, Mikaeloff Y, Tordieu M. Multiple sclerosis in children, clinical diagnosis, therapeutic strategies and future directions. Lancet Neurol 2007;6(10):887-902. 8. Absound M, Lim MJ, Chorg Wk, Goede CGs Foster K, Counny R. Pediatric acquired demyelinating syndromes: incidence, clinical and magnetic resonance imaging features. Mult Scler 2012;19(1):76-86. 9. Banwell B, Krupp L, Kennedy J. Clinical features and viral serology in children with multiple sclerosis: a multinational observation study. Lancet Neurology 2007;6(9):773-81. 10. Jin Y, Depedro-Cusesta J, Söderströ, M. Stawiarz L, Link H. Seasonal pattern in optic neuritis and multiple sclerosis. A meta-analysis. J Neurol Sci 2000;1(181):56-64. 11. Ghobai M, Omrani H, Rosta ئzadeh M. Epidemiology of multiple sclerosis. Tehran Univ Med J 2008;65:74-7. 12. Etemadifar M, Hosseini A, Khodabanehlou R, Maghzi AH. Childhood-onset multiple sclerosis: report of 82 patients from Esfahan, Iran. Arch Iranian Med 2007;10(2):152-6. 13. Ruggior M, Polizzi A, Pervon L, Grimoldi LM. Multiple sclerosis in children under 6 years of age. Neurology 1999;53(3):478-4. 14. Handefield FA. Characteristic of childhood multiple sclerosis. Int MS J 1995;3:91-8. 15. Selcen D, Anlar B, Renda Y. Multiple sclerosis in children. Report of 16 cases. Eur Neurol 1996;36(2):79-84. 16. Inaloo S, Yavari MJ, Sabori S. Multiple sclerosis in children: A review of clinical and paraclinical features in 26 cases. Iran J Child Neruol 2008;2(4):41-6. 17. Hynson JL, Kornberg AJ, Coleman LT, Shield L, Harvey AS, Kean MJ. Clinical and Neuroradiologic feature of acute disseminated encephalomyelitis in children. Neurology 2001;56(13):8-12. 18. Murthy KSN, Faden HS, Cohen ME, Bakshi R. Acute disseminated encephalomyelitis in children. Pediatric 2002;110(2):1-8. 19. Collard RC, Koehler RP, Mattson DH. Frequency and significance of antinuclear antibodies in multiple sclerosis. Neurology 1997;49(3):857-61. 20. Barned S, Goodman AD, Mattson AD. Frequency of antinuclear antibodies in multiple sclerosis. Neurology 1995;45(2):384-5. 21. Sri-Udomkajorn S, Pongwatcharaporn K. Clinical feature and outcome of childhood optic neuritis at Queen Sirikit National Institute of Child Health. J Med Assoc Thai 2011;94(Suppl 3):S189-94. 22. Absoud M, Cummins C, Desai N, Gika A, McSweeney N, Munot P, et al. Childhood optic neuritis clinical features and outcome. Arch Dis Child 2011;96(9):860-2. 23. Thomas T, Branson HM, Verhey LH, Shroff M, Stephens D, Magallhaes S, et al. The demographic, clinical, and magnetic resonance imaging (MRI) features of transverse myelitis in children. J Child Neurol 2012;27(1):11-21